ZAKβ is activated by cellular compression and mediates contraction‐induced MAP kinase signaling in skeletal muscle. (28th July 2022) - Nordgaard, Cathrine; Vind, Anna Constance; Stonadge, Amy; Kjøbsted, Rasmus; Snieckute, Goda; Antas, Pedro; Blasius, Melanie; Reinert, Marie Sofie; Del Val, Ana Martinez; Bekker‐Jensen, Dorte Breinholdt; Haahr, Peter; Miroshnikova, Yekaterina A; et al.
Abstract: Mechanical inputs give rise to p38 and JNK activation, which mediate adaptive physiological responses in various tissues. In skeletal muscle, contraction‐induced p38 and JNK signaling ensure adaptation to exercise, muscle repair, and hypertrophy. However, the mechanisms by which muscle fibers sense mechanical load to activate this signaling have remained elusive. Here, we show that the upstream MAP3K ZAKβ is activated by cellular compression induced by osmotic shock and cyclic compression in vitro, and muscle contraction in vivo . This function relies on ZAKβ's ability to recognize stress fibers in cells and Z‐discs in muscle fibers when mechanically perturbed. Consequently, ZAK‐deficient mice present with skeletal muscle defects characterized by fibers with centralized nuclei and progressive adaptation towards a slower myosin profile. Our results highlight how cells in general respond to mechanical compressive load and how mechanical forces generated during muscle contraction are translated into MAP kinase signaling. Synopsis: Mutations in the MAP3 kinase ZAKβ are associated with progressive muscle weakness in human patients. Here, ZAKβ is shown to protect against myopathy by inducing p38 and JNK signaling in response to mechanical stimuli. ZAKβ is activated by hyperosmotic shock and compressive mechanical stimuli. Mechanical stress‐dependent ZAKβ activation depends on its recruitment to stress fibers in human cell lines and Z‐discs in the skeletal muscle Mice deficient for the ZAK gene show defects in p38 and JNK activation upon skeletal muscle contraction. ZAK knockout mice display muscle pathologies that are reminiscent of human patients mutated in the ZAK gene. Abstract : ZAKβ protects against myopathy by inducing p38 and JNK signaling in response to mechanical stimuli.